2018
DOI: 10.1039/c8cp05855e
|View full text |Cite
|
Sign up to set email alerts
|

Probing chirality recognition of protonated glutamic acid dimers by gas-phase vibrational spectroscopy and first-principles simulations

Abstract: We characterize stereospecific aspects of homochiral and heterochiral dimers of glutamic acid by infrared spectroscopy and first-principles molecular dynamics simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 73 publications
1
27
1
Order By: Relevance
“…The relative populations and IR spectra obtained for individual conformers were used to create a composite spectrum. In order to take into account thermal broadening effects and resolution of IR sources, the absorption bands were then convoluted with Gaussian profile assuming full width at half maximum (FWHM) to be 10 cm −1 for individual conformers at 10 K and 20 cm −1 for combined spectra at room temperature . Noncovalent interaction (NCI) analysis was performed using the Multiwfn program, in order to establish the nature of the bonds that stabilize the complexes.…”
Section: Theoretical Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…The relative populations and IR spectra obtained for individual conformers were used to create a composite spectrum. In order to take into account thermal broadening effects and resolution of IR sources, the absorption bands were then convoluted with Gaussian profile assuming full width at half maximum (FWHM) to be 10 cm −1 for individual conformers at 10 K and 20 cm −1 for combined spectra at room temperature . Noncovalent interaction (NCI) analysis was performed using the Multiwfn program, in order to establish the nature of the bonds that stabilize the complexes.…”
Section: Theoretical Approachmentioning
confidence: 99%
“…To the best of our knowledge, there is only one gas‐phase vibrational spectroscopy study reported, which investigated diastereomer‐specific features of proton‐bound amino acid dimers. That study was carried out for glutamic acid dimers stored in a cryogenic trap held at 10 K …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For larger hydrates (and more flexible organic chromophores), it may be rather difficult to find geometries by hand and, as a consequence, systematic computational sampling techniques such as basin-hopping or molecular dynamics should be employed. [28][29][30] Geometries, energies, and harmonic IR spectra of stable 5HIH + -W n (n = 1-3) and 5HIH + -W-Ar/N 2 (ESI †) structures are calculated at the B3LYP-D3/aug-cc-pVTZ level using GAUSSIAN09. 27,[31][32][33][34] This hybrid density functional with additive dispersion correction has proven to yield reliable results for related aromatic clusters.…”
Section: Experimental and Computational Techniquesmentioning
confidence: 99%
“…The PBE0 functional is frequently used to compute properties of molecular clusters and is less empirical than B3LYP. 28,30,[44][45][46] Furthermore, singlepoint energy calculations of selected optimized structures are performed at the CC2/aug-cc-pVDZ level. Comparison to neutral and cationic s/a5HI-W clusters previously studied at the same level (B3LYP-D3/aug-cc-pVTZ) yields the effects of protonation.…”
Section: Experimental and Computational Techniquesmentioning
confidence: 99%